Year-round colony attendance patterns for the Gentoo Penguin (Pygoscelis papua) at Martillo Island, Tierra del Fuego, Argentina - Dodino, S; Hart, T; Harris, S; Reya Rey, A (Wilson Ornithological Society, 2018)
Long-term monitoring of seabird breeding cycles and breeding success is essential for conservation and a valuable indicator of ecological change, but is logistically expensive and time consuming. We describe the annual cycle and year-round colony attendance patterns for Gentoo Penguins Pygoscelis papua at Martillo Island, Beagle Channel, by analyzing camera trap photographs. We deployed a Reconyx HC500 Hyperfire trail camera programmed in time-lapse mode to take single pictures once per hour year-round (27 Feb 2013 until 27 Feb 2014). The nonreproductive stage began 23 April 2013 when adults completed molt and ended 24 September 2013 when the first pair formation was observed. In general Gentoos Penguins performed daily trips, and the number of adults present at 1900 h ART was not significantly different at any stage except the late chick-rearing and premolt stages. Breeding success was 0.92 chicks per nest. Small variations in day length had a significant influence on penguin's trip duration during the nonreproductive stage. The method proved to be effective for monitoring this species and provided important data for management and conservation.